The possibility of teacher training in hermeneuticalexistential teaching: a reinforcement profile of the teachers in front of the youth fragility exposed to violent religious extremism - Carnevale, Cristina (Formazione & insegnamento, 2017)
In the socio-cultural context, in the West, the school educational agency is facing a complex issue that concerns the impact on the young generation of ideological extremism, particularly in religious matrix, resulting in violent dynamics. The delicate process of development (identity, relational, social) need of a competent formative accompaniment no longer be attributed solely to parental/family function, but due to the professional contribution of the school education agency in respect of values and principles recognized in the constitutions by international human rights declarations. The teacher profile acquires an enhanced educational task that regulate and opens to the real challenge now goes beyond the already obsolete educational service for a balanced development of the personal lives and societies. In this sense, the educational-teaching model hermeneutical-existential, born in reference to the teaching of religion in Italy with the contribution of Prof. Zelindo Trenti (Salesian Pontifical University – Rome), could bring a significant contribution to the initial and in-service teachers of the most prepared for the teaching challenges of the 21st century.